Taxonomic notes of Alpinia subsect. Catimbium (Zingiberaceae) in Vietnam: The first record of Alpinia nobilis and description of a new species Alpinia hoangviet - THI LIEN THUONG NGUYEN; SURAPON SAENSOUK; VAN CANH NGUYEN; VAN KHUONG NGUYEN; THI THANH DAT PHAM; DANG KHOA NGUYEN; DANH DUC NGUYEN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nguyen TLT, Saensouk S, Nguyen VC, Nguyen VK, Pham TTD, Nguyen DK, Nguyen DD. 2023. Taxonomic notes of Alpinia subsect. Catimbium (Zingiberaceae) in Vietnam: The first record of Alpinia nobilis and description of a new species Alpinia hoangviet. Biodiversitas 24: 5293-5301. Alpinia subsect. Catimbium is characterized by the inflorescences being a raceme, panicle or spike; bracts usually absent; prominent bracteoles, if present, almost enclosing the flower buds, calyx deeply split unilaterally, deeply concave labellum usually over 3 cm long and yellow-orange marked crimson red, reduced staminodes being subulate to lightly swollen (nearly absent), and anther usually not crested. The revision of subsect. Catimbium in Vietnam is not completed yet. We estimate that the number of this subsect. is roughly 50% of Catimbium species of the World. As a result of the examination of our living specimens collected during 2019-2022, Alpinia nobilis was defined as a new record in southern Vietnam, and Alpinia hoangviet, a new species belonging to subsect. Catimbium (Zingiberaceae: Alpinieae) from Central Vietnam is described. The taxonomic treatment with a description, photographs, distribution, ecology, conservation assessment, and morphological comparison of the new species with their allies are provided. Moreover, a revised key to all species of Alpinia subsect. Catimbium in Vietnam, is included. Alpinia hirsuta and A. latilabris were eliminated from this key. Alpinia hirsuta is considered a member of subsect. Alpinia, whereas the presence of A. latilabris in Vietnam is a misidentification.